The Effectiveness of Flashcard Media in Improving Student’s Understanding of Tashrif in Morphology : The Effectiveness of Flashcard Media in Improving Student’s Understanding of Tashrif in Morphology (Al-IRTIQA: Journal of Arabic Education and Linguistics, 2026)
Learning Sharaf Science plays an important role in understanding word form changes (tashrif) in the Arabic language. However, this material is often considered difficult due to the large number of patterns that must be understood and the learning methods that tend to be monotonous. Therefore, interesting and easy-to-use learning media are needed to help facilitate the understanding of the material. One of the media that can be used is flashcards, namely learning cards containing brief information presented systematically. The use of flashcards in learning Sharaf Science can help clarify the relationship between root words and their various changed forms, making it easier to understand and remember the material. In addition, this media can also create a more active and enjoyable learning atmosphere. Thus, the use of flashcard media is expected to become an effective alternative in supporting the learning of Sharaf Science, especially in understanding word changes (tashrif).